Altered Chemical Metabolites in the Amygdala-Hippocampus Region Contribute to Autistic Symptoms of Autism Spectrum Disorders - Endo, Taro; Shioiri, Toshiki; Kitamura, Hideaki; Kimura, Teruo; Endo, Sumio; Masuzawa, Naio; Someya, Toshiyuki (Biological psychiatry (1969), 2007)
Although several previous studies have been conducted, the neural basis of autism spectrum disorder (ASD) is poorly understood. The objective of the present study was to determine whether individuals with ASD have altered brain chemical metabolites and whether such alterations are related to their autistic symptoms. N-acetylaspartate (NAA)/creatine (Cr) and choline/Cr ratios in the right medial temporal lobe (MTL), medial prefrontal cortex, and cerebellar vermis were measured in 38 individuals with ASD (mean age = 12.9 years), including 12 with autism, 15 with Asperger’s Disorder, and 11 with pervasive developmental disorder not otherwise specified (PDD-NOS), and 16 matched healthy control subjects (mean age = 11.5 years) with proton magnetic resonance spectroscopy. Autistic symptoms were assessed by the Childhood Autistic Rating Scale-Tokyo Version. There was a significant group difference for NAA/Cr ratio in the right MTL between the autism, Asperger’s Disorder, PDD-NOS, and control groups ( p < .001), and the autism group had a significantly lower NAA/Cr ratio compared with the PDD-NOS ( p < .001) and control ( p < .001) groups. In the ASD group, there was a significant negative correlation between NAA/Cr ratio in the right MTL and their Childhood Autistic Rating Scale-Tokyo Version total scores ( r = −.44, p = .01) and subscales of emotional response ( r = −.38, p = .02) and listening response ( r = −.54, p = .001). The results of the present study suggest that subjects with ASD have abnormalities of neural integrity in the amygdala-hippocampus region that are related to their severity and social impairments.